The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1111/j.1753-4887.2010.00358.x
|View full text |Cite
|
Sign up to set email alerts
|

Dietary fiber type reflects physiological functionality: comparison of grain fiber, inulin, and polydextrose

Abstract: Dietary fiber is a nutritional concept based not on physiological functions but on defined chemical and physical properties. Recent definitions of dietary fiber differentiate inherent plant cell wall-associated fiber from isolated or synthetic fiber. For the latter to be defined as fiber, beneficial physiological effects should be demonstrated, such as laxative effects, fermentability, attenuation of blood cholesterol levels, or postprandial glucose response. Grain fibers are a major natural source of dietary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
158
0
10

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 206 publications
(169 citation statements)
references
References 124 publications
(239 reference statements)
1
158
0
10
Order By: Relevance
“…Mateos et al (2012) concluded that the potential responses to fibre inclusion might rely on the source and level of DF and the properties of the diet as well as on the physiological status and health of the bird. The levels of DF might bring about the differences in GIT transit rates, pH values, and volatile fatty acid productions in poultry (Raninen et al 2011). Consequently, DF level might affect voluntary feed intake, organ size, GIT motility, enzyme production, nutrient digestibility, microbial growth, and growth performance.…”
mentioning
confidence: 99%
“…Mateos et al (2012) concluded that the potential responses to fibre inclusion might rely on the source and level of DF and the properties of the diet as well as on the physiological status and health of the bird. The levels of DF might bring about the differences in GIT transit rates, pH values, and volatile fatty acid productions in poultry (Raninen et al 2011). Consequently, DF level might affect voluntary feed intake, organ size, GIT motility, enzyme production, nutrient digestibility, microbial growth, and growth performance.…”
mentioning
confidence: 99%
“…Soluble viscous fiber plays an important role in controlling satiety and postprandial glycemic and insulin responses [68] and some studies showed that insoluble dietary fiber improved the quality of life for these patients [69] The protective effect of DF on obesity and T2DM has been historically attributed to greater satiety due to an increased mastication, calorie displacement, and decreased absorption of macronutrients [55]. This mechanism is associated with the ability of soluble fibers to form viscous solutions that prolong gastric emptying, consequently inhibiting the transport of glucose, triglycerides and cholesterol across the intestine [70][71][72]. Recently, it was observed that both soluble and insoluble DFs also modifies carbohydrate metabolism by influencing the expression of hormones such as glucose-dependent insulin tropic polypeptide and glucagon-like peptide-1, that stimulate postprandial insulin release, enhance glucose tolerance, and delay gastric emptying [73][74][75][76].…”
Section: Fiber Carbohydrate Metabolism and Diabetes Mellitusmentioning
confidence: 99%
“…Later definitions of fiber in nutrition have also included isolated fibers from food raw materials or edible synthetic carbohydrates that are resistant to digestion and absorption in the human small intestine but are partly or completely fermentable in the colon, and display beneficial physiological effects, i.e., improved bowel function, blood cholesterol, and blood glucose attenuation (Raninen et al, 2011). These beneficial effects, i.e., improvements in metabolic and disease control, are essentially based on the dominant attributes of different fiber types when passing through the gastrointestinal tract.…”
Section: Dietary Fiber and Glycemic Controlmentioning
confidence: 99%
“…Several classifications for fiber have been established (Slavin et al, 2009;Raninen et al, 2011) in which the traditional one is based on water solubility dividing fiber into soluble (pectins, gums, mucilages) and insoluble (cellulose, hemicelluloses, lignin) fiber types. Although solubility per se is an essential determinant of the physiological responses, viscosity and fermentability are likely to play a more pronounced role in the physiological benefits in humans.…”
Section: Dietary Fiber and Glycemic Controlmentioning
confidence: 99%